Microstructure and mechanical and corrosion properties of hot-extruded Mg–Zn–Ca–(Mn) biodegradable alloys - V.E. Bazhenov; A.V. Li; A.A. Komissarov; A.V. Koltygin; S.A. Tavolzhanskii; V.A. Bautin; O.O. Voropaeva; A.M. Mukhametshina; A.A. Tokar (Journal of Magnesium and Alloys, 2021)
Biodegradable Mg-based implants are widely used in clinical applications because they exhibit mechanical properties comparable to those of human bone and require no revision surgery for their removal. Among Mg-based alloys, Mg–Zn–Ca–(Mn) alloys have been extensively investigated for medical applications because the constituent elements of these alloys, Mg, Zn, Ca, and Mn, are present in human tissues as nutrient elements. In this study, we investigated the effect of the hot extrusion temperature on the microstructure, mechanical properties, and biodegradation rate of Mg–Zn–Ca–(Mn) alloys. The results showed that the addition of Mn and a decrease in the extrusion temperature resulted in grain refinement followed by an increase in the strength and a decrease in the elongation at fracture of the alloys. The alloys showed different mechanical properties along the directions parallel and perpendicular to the extrusion direction. The corrosion test of the alloys in the Hanks’ solution revealed that the addition of Mn significantly reduced the corrosion rate of the alloys. The Mg–2 wt% Zn–0.7 wt% Ca–1 wt% Mn alloy hot-extruded at 300 °C with an ultimate tensile strength of 278 MPa, an yield strength of 229 MPa, an elongation at fracture of 10%, and a corrosion rate of 0.3 mm/year was found to be suitable for orthopedic implants.